Green solvents assisted de-novo synthesis and defect-engineered UiO-66 for improved CO2 adsorption and kinetics- experimental and DFT approach - Saleem Nawaz Khan; Ming Zhao (Carbon Capture Science & Technology)
The CO2 concentration in the atmosphere is increasing at an alarming rate, which is causing distress to human society and the natural environment. Adsorption is one of the most widely used methods of removing CO2 from flue gases, which reduces its adverse effects on our environment. For adsorption purposes, a facile green solvent-assisted de-novo synthesis approach was developed to construct a UiO-66′s structure to target CO2 at low pressure due to the partial pressure of CO2 in flue gases in the atmosphere (0.01⁓0.02 MPa). In the de-novo synthesis approach, a combination of various types of modulators and deep eutectic solvents (DES) are utilized to graft structural defects and induce quantitative and dispersive deep eutectic solvents onto the UiO-66 structure, respectively. The green solvent-assisted de-novo synthesis approach helped to tune all three structural parameters and preserve extra open metal sites (Lewis acid and Bronsted basis sites) with active NH2 and OH groups for improved CO2 adsorption and kinetics under flue gas conditions (CO2/N2=15/85 %). In comparison to the parent UiO-66, de-novo synthesized ChClPropx5@UiO-66 showed increased CO2 uptake (65.04 mg g-1) by 73 % at 0.15 bar and 25 °C, and the cyclic capacity remained almost similar over 10 consecutive cycles with an almost 94 % retention rate. After 3 times of regeneration at 105 °C under N2 atmosphere, the sample reserved almost similar adsorption capacity and could be recycled without dropping CO2 uptake. The strong and rapid interaction between guest CO2 and de-novo synthesized UiO-66 was confirmed by pseudo-first-order and second-order kinetics with reaction rate constants of 0.00026 and 0.00259, respectively. Furthermore, through periodic Density Functional Theory (DFT) calculations, a variety of linker defects are engineered onto the UiO-66 structure to preserve more open metal sites. For each of the engineering defects, free energies, adsorption energies, and the interaction of CO2 molecules on defect structures with bond length (Ɩ, Å) and bond angle (θ˚) are calculated for the most stable structures of UiO-66.